Effect of nation-wide lock-down due to Covid-19 over industrial pollution in Delhi, India. (2021) - Kumar, Harish; Arora, Ranjan; Kumar Arora, Pawan; Pandey, V.S.; Moona, Girija; Singh, Deepak
Abstract: In India, very first infection due to Covid-19 was reported by end of January 2020 and, the same has been increased with the span of time. In order to fight the increasing risk among the citizens of nation, the complete lock-down was declared on March 25, 2020 for initially 21 days and thereafter it has been subsequently increased up to its present 4th phase, which would be remain continue until May 31, 2020. First two phases of lock-down were imposed without any relaxation, however, there were gradual relaxation implemented in third and fourth lock-down phases. Air pollution depends on emission of the pollutants from vehicles and industries, as well as dust from construction activities. Due to lock-down, operations concerning these activities were completely shut down. The effect of lock-down on PM2.5, PM10, NO2, SO2, CO and AQI level was studied and comparison of PM2.5, PM10, NO2, SO2, CO and AQI during lock-down with same dates of previous year was also considered.